Analisis Unsur Intrinsik Pada Film “Mencuri Raden Saleh” - Yusril Dava Bayu; Annisa Rizqiani; Ida Sakura (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Literary works are creative expressions that focus on the human experience and life, utilizing language as a means of communication. Furthermore, literature is the outcome of human creativity conveyed via the use of writing and language as a means of communication. Literature is essentially a form of artistic expression by humans that use language as a medium to convey experiences, thoughts, feelings, and ideas. Common literary works encountered in daily life include short tales, poems, novels, films, and dramas. The aim of this research is to identify the inherent components contained in the film